Teacher Skill Improvement Training in Conducting Information Technology System-Based Learning and Communication in Vocational High Schools - M. Choerul Umam; Dyah Sulistyaningrum Indrawati; Patni Ninghardjanti; Anton Subarno; Winarno Winarno (STAIFAS-Press, 2022)
Teachers at vocational schools are facilitators in implementing an effective learning process. The learning process is inextricably linked to the media, methods and learning outcomes. In this case, the media play an important role. As we know, online learning platforms are very diverse, but not all of these platforms can be used effectively to create meaningful, interesting and interactive learning in office administration. The objectives of Training to Improve Teacher Skills in Conducting Information Technology Based Learning and Communication in Vocational Schools are 1) Improve Teacher Skills in Development of Innovative Learning Models 2) Improve Teacher Skills in Development of Learning Management System (LMS) to become Professional and Competent Teachers who design learning media and implement them in learning activities. 3) Improving teachers' communication skills in learning through live virtual meetings and live chat through Whatsapp desktop application in vocational schools. The results of the training were: 1) Increasing the ability of teachers to develop innovative learning models by 80%, 2) Increasing the ability to develop a Znaplink-based Learning Management System (LMS) by 86%, and 3) The Improving the ability of teachers to communicate while learning through live virtual meetings and live chats with Whatsapp desktop application has reached 88%.